2022
DOI: 10.1039/d2sm01215d
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying the trade-off between stiffness and permeability in hydrogels

Abstract: Hydrogels have a distinct combination of mechanical and water-transport behaviors. As hydrogels stiffen when they de-swell, they become less permeable. Here, we combine de Gennes' semi-dilute polymer theory with the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Previously, we investigated the changes in permeability and stiffness with crosslinking and found that any changes in permeability are nearly inverse with any changes in stiffness. 22 Thus, across different crossslinker ratios, the poroelastic diffusion coefficient remains relatively constant, as shown in Fig. S1 (ESI †).…”
Section: Introductionmentioning
confidence: 82%
“…Previously, we investigated the changes in permeability and stiffness with crosslinking and found that any changes in permeability are nearly inverse with any changes in stiffness. 22 Thus, across different crossslinker ratios, the poroelastic diffusion coefficient remains relatively constant, as shown in Fig. S1 (ESI †).…”
Section: Introductionmentioning
confidence: 82%
“…2014; Rahbari et al. 2017; Gao & Cho 2022). We compare it with a simpler power-law formulation in Appendix A, showing that the two are qualitatively and quantitatively similar and are expected to produce similar behaviour.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…2014; Rahbari et al. 2017; Gao & Cho 2022 and power law in Holmes & Mow 1990; Ehlers et al. 2009; Sengers et al.…”
Section: Figure 12mentioning
confidence: 99%
“…It is evident that a trade-off relationship exists between some of the mechanical properties (such as compressive modulus) and transport properties for separation membranes, and the improvement of transport properties through increased porosity inevitably leads to a compromise in compressive modulus and vice versa . The same issue also limits the application of a broad range of functional materials involving macroporous polymers, such as biological scaffolds in tissue engineering, hydrogels, polymer foam armors, and heat-transfer porous materials . In all of these applications, it is crucial for the porous polymer to possess both mechanical robustness and sufficient porosity to facilitate fast transport or permeation, ,, but this trade-off phenomenon has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%